Stanowisko Polskiego Towarzystwa Okulistycznego określające standardy prowadzenia terapii pacjentów z wysiękową postacią starczego zwyrodnienia plamki - Misiuk-Hojło, Marta; Bakunowicz-Łazarczyk, Alina; Dobrowolski, Dariusz; Grabska-Liberek, Iwona; Mackiewicz, Jerzy; Mrukwa-Kominek, Ewa; Nowak, Agnieszka; Pociej-Marciak, Weronika; Romanowska-Dixon, Bożena; Stopa, Marcin; Szaflik, Jacek; Kałużny, Jakub; et al. (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Age-related macular degeneration (AMD) is a leading cause of impairment of vision in the population over 50 years of age in developed countries. The most important risk factors for the development of AMD include increasing age, living in northern regions of Europe, genetic factors and smoking. The recommendations support the use of supplements (antioxydants), intravitreal injection of anti-VEGF agents and photodynamic therapy (PDT). Anti-VEGF therapy (e.g., aflibercept, bevacizumab, ranibizumab, brolucizumab, faricimab) is the most effective way to manage neovascular AMD and represents the first line of treatment. In patients with neovascular AMD, early detection and prompt treatment improves the visual outcome. This paper presents the current treatment standards for neovascular AMD developed by a group of experts from the Polish Ophthalmological Society.